Different C2 Screw Placement Technique Wıth Mobilization of the Vertebral Artery In High-Riding Vertebral Artery Cases: Cadaver Dıssectıon - HARMAN, FERHAT; OĞLİN, VOLKAN; DAĞÇINAR, ADNAN (My University, 2023)
Aim: In neurosurgery, posterior approaches intended at the craniovertebral junction are frequently used. The most popular procedures for treating upper cervical instability are C1 lateral mass, C2 pedicle, and C1-C2 transarticular screw stabilization. Due to their proximity to neural structures and the presence of the high-riding vertebral artery, these techniques are complicated. By mobilizing the vertebral artery, the risk of VA damage can be decreased. Using cadaveric specimens in this study was aimed to demonstrate C2 pedicle and C1-C2 transarticular screw placement with vertebral artery mobilization and a novel C2 screw placement technique Method: In this study, twelve adult cadaveric specimens and two adult dry cadaveric C2 bones were used with the permission and decision of the University Research Ethics Committee. Colored silicone was injected into the arteries and veins of these twelve cadaveric specimens. Then, muscle dissection was performed stepwise, and the C2 vertebrae of the cadavers were revealed with a Surgical Microscope. Each specimen and entire stages of the dissections were recorded photographically. After cadaver dissections were completed and screw placement was performed with three different techniques, radiological imaging was done with fluoroscopy. Results: After dissection, the lateral mass of the C2 vertebra was observed, and lateral to it the transverse process and foramen were detected with the help of a hook. Next, the posterior wall of the vertebral artery groove was removed until the vertebral artery loop could partially be observed to mobilize the vertebral artery using a 1 mm thin plate Kerrison rongeur. This enables us to find the top of the loop of the vertebral artery and mobilize it inferiorly by using a dissector. Following this step, the C1-2 transarticular, C2 pedicle, and the novel C2 inferior corpus screw placement can be performed safely by directly visualizing the artery (Figure 1). Conclusion: Due to the nearby neurologic and vascular structures, placing the C2 pedicle and C1-2 transarticular screw is a challenging procedure, especially in high-riding vertebral artery cases. However, it is possible to place the C2 pedicle, C1-2 transarticular, and novel C2 inferior corpus screw after the mobilization of the vertebral artery. This study aimed to show all of them together on a cadaver for the first time, to understand the anatomy of the C2 vertebra, and to use screw placement techniques to minimize the risk of complications.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)